Slowly digestible sweetpotato flour: Preparation by heat-moisture treatment and characterization of physicochemical properties - Ahn, Ji Hong; Baek, Hye Rim; Kim, Kyung Mi; Han, Gui Jung; Choi, Jun Bong; Kim, Yang; Moon, Tae Wha (Food science and biotechnology, 2013)
The preparation and physicochemical characteristics of sweetpotato flour with increased slowly digestible starch (SDS) fraction were investigated under various heat-moisture treatment (HMT) conditions. The optimum conditions for preparing slowly digestible sweetpotato flour established using response surface methodology were moisture content of 22%, temperature of 103°C, and treatment time of 5.8 h. The highest SDS content in heat-moisture treated sweetpotato flour was 57.6%. The relative crystallinity of heat-moisture treated sweetpotato flour decreased, but the X-ray diffraction pattern maintained the A-type. The DSC of the heatmoisture treated flour showed a decreased gelatinization temperature range and gelatinization enthalpy compared with native one. The viscosity profiles and values changed significantly with HMT, resulting in a higher pasting temperature, decrease of the viscosity values, and no breakdown. It indicates that heat-moisture treated sweetpotato flour is more stable at high temperatures and shear rates than native one.